Laccase production by locally-isolated Trichoderma sp. IS1037 using rubberwood dust for biobleaching of soda bamboo pulps - Jaber, Saja Mahdey (2017)
Conventional pulp bleaching of lignocellulosic materials using chlorine and its compounds leads to the generation of toxic compounds including chlorolignins. Therefore a study on biobleaching of lignocellulosic material was carried out as an alternative for pulp bleaching purpose. This study focused on the use of laccase from Trichoderma sp. IS1037 for bamboo pulp biobleaching. The laccase enzyme was produced from a local fungi isolate Trichoderma sp. IS1037. The possibility of using crude laccase for bleaching bamboo soda pulp by combining it with bleaching chlorine agents was also studied. A total of five native fungi was screened to determine the potential producer of laccase enzyme. The fungi isolate was identified by utilizing the Biolog Kit and molecular assay. Optimization of culture condition for laccase production was carried out using seven selected parameters known as carbon source, nitrogen source, temperature, pH, agitation speed, concentration of CuSO4, and surfactant. The crude laccase produced was used for the pretreatment of bleaching process on unbleached bamboo soda pulp. Optimization of temperature, pH and reaction time on crude laccase pretreatment of bamboo pulp was investigated using response surface method (RSM) followed by chemical bleaching sequences D1EPD2. In order to evaluate the decrease in lignin content, adsorbable organic halogens (AOX), hexenuronic acid (HexA) and chemical oxygen demand (COD) were tested. Solid phase extraction was conducted to extract AOX from effluent after bleaching process and HPLC was aplied to determine AOX concentration. HexA was conducted using UV spectrophotometer. The result from screening demonstrated that laccase produced from locally isolated fungi identified as Trichoderma sp. IS1037 under optimized condition was 65.0 U/ml which is 11 fold higher than the production of the control culture 5.8 via submerged fermentation strategy. The optimum condition for laccase production was 30 °C, 4.5 and 150 rpm for temperature, initial pH media and agitation speed, respectively, using rubberwood dust as a carbon source together with organic nitrogen source (peptone, yeast extract and malt extract). The effects of copper sulphate and Tween 80 were found significant in improving the extracellular laccase production. In pretreatment of bamboo pulp using laccase under optimized condition has decreased lignin by 64% and hemicellulose by 50% content was achieved at pH, temperature and reaction time of 4, 50 °C and 4 hours, respectively. XRD and FTIR analysis showed an increase in relative crystallinity of cellulose and delignification due to hydroxylation and exfoliation of amorphous regions through laccase pretreatment. In addition, there were significant result found in the reduction of AOX, COD, HexA and lignin by the enzymatic pretreatment. The AOX content of bamboo pulp was reduced by 29%, 34% for biobleaching and modified sample respectively. Moreover, HexA results revealed decrement in content with 1.44% to 1.42% for biobleaching and modified sample respectively. Therefore, the pretreatment of bamboo pulp by laccase has considerable benefit on reducing the organic compound of AOX, COD, HexA and chemical composition in different sequence bleaching. The outcomes presented in this study could contribute to the future study on the production of laccase enzyme from Trichoderma sp.IS1037 for various industrial applications including pulp and paper industry.